REVIEW ON THE APPLICATION OF OPEN BANKING IN SHARIA BANKING: AN SWOT ANALYSIS - Egha Ezar Junaeka Putra Hassany; Galuh Tri Pambekti (el-Amwal, 2022)
This study was conducted to analyze SWOT (Strength, Weakness Opportunity, and Threat) Open Banking in Islamic banking in Indonesia. The analytical method used is descriptive literature research, namely by providing a description or description of the problems that have been identified and carried out intensively and in detail on a problem from the available literature. The results of this study indicate that there are several strategies that can be taken by Islamic Banking in dealing with Open Banking, including the S-O strategy: cooperation with fintech and e-commerce; and expand the network of cooperation nationally and internationally; W-O strategy: socializing open banking, improving technology and security, and increasing service complaints; S-T strategy: cooperate with other financial institutions, implement standardization prepared by the regulator; and W-O Strategy: multiple security enhancements, sorting out cooperation to third parties, and upgrading Islamic banking internal servers.